2002
DOI: 10.1002/ijc.10295
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumor targeting: Study of novel gallium‐labeled somatostatin radiopeptides in a rat pancreatic tumor model

Abstract: Somatostatin analogs labeled with radionuclides are of considerable interest in the diagnosis and therapy of SSTRexpressing tumors, such as gastroenteropancreatic, small cell lung, breast and frequently nervous system tumors. In view of the favorable physical characteristics of the Ga isotopes 67 Ga and 68 Ga, enabling conventional tumor scintigraphy, PET and possibly internal radiotherapy, we focused on the development of a Ga-labeled somatostatin analog suit- SSTRs are overexpressed by a variety of neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 28 publications
5
70
2
1
Order By: Relevance
“…The fact that for all of the fluorinated TOCA derivatives Ͼ96% of the initial cellular activity was externalized within 60 min under conditions inhibiting recycling (5 M TOC) indicates a negligible extent of intracellular ligand residualization. This represents one major disadvantage of radiohalogenated over radiometallated octreotide analogs, of which the charged radiometal-chelate-containing fragments remain trapped in the lysosomal compartments after degradation (7,47,48). The high extent of apparent intracellular retention of [ F-labeled TOCA derivatives in this study between 10 and 60 min p.i.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The fact that for all of the fluorinated TOCA derivatives Ͼ96% of the initial cellular activity was externalized within 60 min under conditions inhibiting recycling (5 M TOC) indicates a negligible extent of intracellular ligand residualization. This represents one major disadvantage of radiohalogenated over radiometallated octreotide analogs, of which the charged radiometal-chelate-containing fragments remain trapped in the lysosomal compartments after degradation (7,47,48). The high extent of apparent intracellular retention of [ F-labeled TOCA derivatives in this study between 10 and 60 min p.i.…”
Section: Discussionmentioning
confidence: 70%
“…Due to the ease of radiometallation, a variety of chelatorcoupled octreotide derivatives have been labeled with positronemitting radiometals such as 86 Y (1-3), 64 Cu (4 -6), and 66/68 Ga (7)(8)(9)(10). Initial patient PET studies using 64 Cu-triethylenetetraamine-octreotide as well as [ 66 (3).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, gamma-based SRS has reported sensitivity and specificity for non-insulinoma pancreatic NETs of approximately 80%-90% [86,87] , and is indicated for use in pre-therapy localization and staging, especially when demonstration of extra-hepatic metastatic lesions is required. Several reports have established the promising utility of PET-based SRS for imaging non-insulinoma pancreatic NETs [88][89][90] . The use of PET-based SRS is expected to have improved resolutive capabilities as compared with conventional gamma-based SRS, in keeping with findings from gastrointestinal carcinoid imaging, but further validation is needed.…”
Section: Functional Imaging Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
“…68 Ga-DOTATATE has high affinity for SSR-2, is rapidly excreted from nontarget sites, offers good target to nontarget imaging properties, and hence is an ideal potential candidate tracer for imaging NETs. [2][3][4][5] Recent studies have indicated that 68 Ga-labeled DOTA peptide DOTATOC has potential to improve imaging for NET over conventional 111 indium pentetreotide. [5][6][7] NETs, however, typically have a wide range of cellular differentiation.…”
mentioning
confidence: 99%